Knowledge and Attitude Regarding Major Risk Factors of Cardiovascular Diseases among 15-19 Year Old Students of Kathmandu District - Yadav, KD; Wagle, RR (Health Prospect, 2018)
Background: Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. Studies have shown that some people are at greater risk of developing cardiovascular disease than others. The major factors which increase the risks are tobacco chewing/smoking, raised blood cholesterol level, high blood pressure, physical inactivity, overweight and obesity, excessive alcohol consumption, age, sex and heredity. Although cardiovascular diseases typically occur in middle age or later, risk factors are determined to a great extent by behaviours learnt in childhood and continued into adulthood. Throughout the world, these risks are starting to appear earlier. Findings of various studies worldwide suggested that adolescents lacked knowledge regarding the risk of cardiovascular diseases and did not perceive themselves at risk for cardiovascular diseases. Methodology: A cross-sectional study was conducted among 144 adolescent students of grade XI and XII in one public and one private higher secondary schools of Kathmandu district. Samples were chosen purposively. Data were collected with the help of semi structured self administered questionnaire. Questionnaire was based on Likert scale. Data analysis was performed by using Statistical Package for Social Science - 17.0 for windows. Results: Overall 36.8 percent of respondents had good knowledge, 55.6 percent had fair knowledge and the remaining 7.6 percent had poor knowledge regarding the major risk factors of cardiovascular diseases. Sources of health information was found statistically significant (p=0.004) with the knowledge of respondents. Regarding overall attitude, the majority (47.9%) had the neutral attitude followed by positive (31.9%) and one fifth possessed negative attitude. Knowledge versus attitude regarding the major risk factors of cardiovascular diseases was found statistically significant (p=0.002). Conclusion: Results of this study revealed that good knowledge as well as positive attitude towards major risk factors of cardiovascular diseases among the adolescent students is unsatisfactory. Socio-demographic factors for good knowledge and good knowledge for the development of positive attitude play vital role. DOI: http://dx.doi.org/10.3126/hprospect.v11i0.7422 Health Prospect 2012;11:7-10